EFFORTS TO IMPROVE STUDENTS' ABILITY TO READ YELLOW BOOKS USING THE AMSILATI METHOD - Anwar Sholeh; M.Basori Alwi; Nurul Widya Agustin; Ahmad Fuad Abdul Baqi (International Journal of Multidisciplinary Reseach, 2025)
The purpose of this study is to describe the learning of yellow books using the fast reading method, namely the Amsilaty method. The subjects of this study were class 2 Tsanawiyah Madrasah Diniyah Riyadlus Sholihin, Probolinggo City. This study uses Classroom Action Research and is included in the scope of applied research that combines knowledge, research and action. This study uses two cycles, each consisting of planning, implementation, observation and reflection. The data collection technique uses document studies in the initial conditions. The results of the study indicate that the use of the Amsilaty method in learning to read yellow books provides an increase in the ability to read yellow books of students in class 2 Tsanawiyah Madrasah Diniyah Riyadlus Sholihin, Probolinggo City. In the initial conditions it only reached 51%, then in the first cycle it increased to 90% and in the second cycle it increased to 95%.